THE JEWISH SOURCE OF ROM 5:17, 16, 10 AND 9: The Verses of Paul in Relation to a Comment in the Mishnah at m. Makk 3.15 - Collins, Nina L. (Revue biblique, 2005)
A close examination of the statements of Paul at Rom 5:9, 10, 16 and 17 suggests that these verses were originally inspired by a Hebrew precursor of a rabbinic text, which has been preserved in the Mishnah at Makk 3.15. These words of Paul also reveal a thematic development in Paul's thought, in a progression which reverses their logical order in Paul's present text. It is possible therefore that they were composed by Paul before they were used in that part of his letter in which they now lie. The study as a whole also demonstrates the use of a Jewish source for the understanding of Paul, along with the value of the New Testament for the history and interpretation of an ancient rabbinic thought. Un examen des affirmations de Paul en Rom 5, 9, 10, 16 et 17, suggère que ces versets se sont inspirés d'un texte hébreu, précurseur d'une argumentation rabbinique, – laquelle nous a été préservée dans la Mishna, en Makk. 3,15. Ces mots de Paul révèlent une évolution thématique de la pensée de l'Apôtre, dans une progression inverse à l'ordre du texte actuel. Il est dès lors possible qu'ils aient été écrits par Paul avant qu'ils ne soient utilisés dans l'actuelle Épître. L'étude illustre non seulement l'utilisation d'une source juive pour la compréhension de Paul, mais aussi la valeur du Nouveau Testament pour l'histoire et l'interprétation d'une pensée rabbinique ancienne.